DIGITAL EDUCATION: ENSURING EQUITABLE USE OF TECHNOLOGY (International Journal of Food and Nutritional Sciences, 2021)
Education is fundamental for achieving full human potential, developing an equitable society, and promoting national development. India is a global leader in information and communication technology and in other cutting-edge domains. The Digital India Campaign is helping to transform the entire nation into a digitally empowered society and knowledge economy. Education on one hand will play a critical role in this transformation; technology itself on the other hand, will play an important role in the improvement of educational processes and outcomes. Thus, the relationship between technology and education at all levels is bidirectional. The proliferation of digital technologies in recent times is bringing radical changes in the way education is being delivered and received. The outreach of educational programs is improving day by day with the digitalization of education. However, the benefits of online/digital education cannot be leveraged unless the digital divide is eliminated. It is important that the use of technology for online and digital education adequately addresses concerns of equity. This paper delves into the trends of digital education in India, equitable access to technology for eliminating the digital divide and the various blockers that hinders and enablers that promote acquisition of equitable digital education.